Antimicrobial activity against oral pathogens and immunomodulatory effects and toxicity of geopropolis produced by the stingless bee Melipona fasciculata Smith - Liberio Silvana A; Pereira Antônio Luís A; Dutra Richard P; Reis Aramys S; Araújo Maria José AM; Mattar Nadia S; Silva Lucilene A; Ribeiro Maria Nilce S; Nascimento Flávia Raquel F; Guerra Rosane NM; Monteiro-Neto Valério (BMC, 2011)
Abstract Background Native bees of the tribe Meliponini produce a distinct kind of propolis called geopropolis. Although many pharmacological activities of propolis have already been demonstrated, little is known about geopropolis, particularly regarding its antimicrobial activity against oral pathogens. The present study aimed at investigating the antimicrobial activity of M. fasciculata geopropolis against oral pathogens, its effects on S. mutans biofilms, and the chemical contents of the extracts. A gel prepared with a geopropolis extract was also analyzed for its activity on S. mutans and its immunotoxicological potential. Methods Antimicrobial activities of three hydroalcoholic extracts (HAEs) of geopropolis, and hexane and chloroform fractions of one extract, were evaluated using the agar diffusion method and the broth dilution technique. Ethanol (70%, v/v) and chlorhexidine (0.12%, w/w) were used as negative and positive controls, respectively. Total phenol and flavonoid concentrations were assayed by spectrophotometry. Immunotoxicity was evaluated in mice by topical application in the oral cavity followed by quantification of biochemical and immunological parameters, and macro-microscopic analysis of animal organs. Results Two extracts, HAE-2 and HAE-3, showed inhibition zones ranging from 9 to 13 mm in diameter for S. mutans and C. albicans, but presented no activity against L. acidophilus. The MBCs for HAE-2 and HAE-3 against S. mutans were 6.25 mg/mL and 12.5 mg/mL, respectively. HAE-2 was fractionated, and its chloroform fraction had an MBC of 14.57 mg/mL. HAE-2 also exhibited bactericidal effects on S. mutans biofilms after 3 h of treatment. Significant differences (p < 0.05) in total phenol and flavonoid concentrations were observed among the samples. Signs toxic effects were not observed after application of the geopropolis-based gel, but an increase in the production of IL-4 and IL-10, anti-inflammatory cytokines, was detected. Conclusions In summary, geopropolis produced by M. fasciculata can exert antimicrobial action against S. mutans and C. albicans, with significant inhibitory activity against S. mutans biofilms. The extract with the highest flavonoid concentration, HAE-2, presented the highest antimicrobial activity. In addition, a geopropolis-based gel is not toxic in an animal model and displays anti-inflammatory effect.